Listening to the bats of Carajás: Bioacoustics in a mosaic of forests, savannas, and industrial mining in the Brazilian Amazonia - LIDIANE GOMES; ENRICO BERNARD (Anais da Academia Brasileira de Ciências)
Abstract Bats emit echolocation calls for orientation, foraging, and social interactions. These calls are mostly species-specific, making them reliable for inventories and assessing habitat use – characteristics particularly useful in large, species-rich, but poorly sampled areas. This is the case of Carajás, in Brazilian Amazonia, a mosaic of cave-rich dense forests and unique metalophilous savannas (known as canga), harboring a rich bat fauna alongside industrial iron ore mining, underscoring the need to preserve biodiversity. We used bioacoustics (142,000 minutes of recording) to inventory bats at 61 points in Carajás between 2021 and 2023, and identified 43 sonotypes of seven bat families, including species rarely recorded with capture nets. Eleven species were recorded for the first time in Carajás. Species richness varied among habitats – but cangas had greater richness stability and a more distinct species composition. All areas with imminent mining had high bat richness. Richness in a post-mined area increased, possibly indicating resilience of some species. By providing a reference sound library for bats in Carajás, we proved the usefulness of biacoustics to improve the environmental licensing processes involving mining in biodiversity-rich areas, useful not only for Amazonia but also for other tropical habitats with high bat species richness.